Corrections to "Risk Analysis of Cloud Sourcing in Healthcare and Public Health Industry" - Abrar, Hina; Hussain, Syed Jawad; Chaudhry, Junaid; Saleem, Kashif; Orgun, Mehmet A.; Al-Muhtadi, Jalal; Valli, Craig (IEEE access, 2021)
In above article [1] , reference [11] is incorrect as the conference article had not been published in full until 2019. The correct reference is cited here as [2] . Therefore, the sentences in the article [1] with reference [11] should be cited [2] in this article as "When the data are stored in a centralized location and are transmitted by applying symmetric data encryption techniques, the deployment and maintenance costs will go beyond cost tolerance thresholds [2] ," "Since cloud computing signifies a comparatively novel computing representation at every level, like applications, hosts, network, and data, that in turn raises the issue of the application safety to shift toward cloud computing [2] and [3] ," and "However, this definition is not accurate in the sense that, if the normal operation is susceptible to eavesdropping, in this case, the normal operation of the organization must be restricted [2] ."